Genotype and Environment Effects on Prebiotic Carbohydrate Concentrations in Kabuli Chickpea Cultivars and Breeding Lines Grown in the U.S. Pacific Northwest - Vandemark, George; Thavarajah, Samadhi; Siva, Niroshan; Thavarajah, Dil (Frontiers in Plant Science, 2020)
Prebiotic carbohydrates are compounds that include simple sugars, sugar alcohols, and raffinose family oligosaccharides, which are fermented by gut bacteria and can influence the species profile of the gut microbiome to reduce obesity and weight gain. Fermentation of prebiotic carbohydrates produces short chain fatty acids that are associated with several health benefits including reduced obesity and insulin dependence and protection against development of colorectal cancer. Although pulse crops such as chickpea have served as important sources of nutrition for human diets for thousands of years, relatively little is known about the profiles of prebiotic carbohydrates in seeds of pulse crops. The objectives of this study were to characterize the type and concentration of seed prebiotic carbohydrates in 24 kabuli genotypes grown in Idaho and Washington, and partition variance components conditioning these nutritional quality traits in chickpea. Significant genetic effects were detected for concentrations of several prebiotic carbohydrates, including mannitol, sucrose, and raffinose. Genetic effects explained the majority of total variance for sucrose concentration, suggesting this trait could be improved using adapted materials as parents. However, for other prebiotic carbohydrates genetic effects were either not significant or were of less magnitude than environmental effects. Genotype x environment interaction effects were not significant for any prebiotic carbohydrates. Overall, our results suggest that a survey of more genetically diverse plant materials, such as a chickpea ‘mini-core’ collection, may reveal genotypes that produce significantly greater concentrations of selected prebiotic carbohydrates and could be used to introduce desirable nutritional traits into adapted chickpea cultivars.